Surfactants: Role in biofilm management and cellular behaviour. Issue 3 (18th March 2019) - Percival, Steven L.; Mayer, Dieter; Kirsner, Robert S.; Schultz, Greg; Weir, Dot; Roy, Sashwati; Alavi, Afsaneh; Romanelli, Marco
Abstract : Appropriate and effective wound cleaning represents an important process that is necessary for preparing the wound for improved wound healing and for helping to dislodge biofilms. Wound cleaning is of paramount importance to wound bed preparation for helping to enhance wound healing. Surfactant applications in wound care may represent an important area in the cleaning continuum. However, understanding of the role and significance of surfactants in wound cleansing, biofilm prevention and control, and enhancing cellular viability and proliferation is currently lacking. Despite this, some recent evidence on poloxamer‐based surfactants where the surfactants are present in high concentration have been shown to have an important role to play in biofilm management; matrix metalloproteinase modulation; reducing inflammation; and enhancing cellular proliferation, behaviour, and viability. Consequently, this review aims to discuss the role, mode of action, and clinical significance of the use of medically accepted surfactants, with a focus on concentrated poloxamer‐based surfactants, to wound healing but, more specifically, the role they may play in biofilm management and effects on cellular repair.